A sequential explanatory mixed methods study on the relationships of degression and generalised anxiety disorder, with levels of alcohol consumption in order adults - FULHAM-MCQUILLAN, HUGH (Trinity College Dublin. School of Nursing & Midwifery. Discipline of Nursing, 2020)
Background: Depression and generalised anxiety disorder (GAD) in the older adult population (aged 65 and over) are underdiagnosed and undertreated, as is harmful drinking. The relationships of depression, and GAD, with alcohol consumption are commonly assumed. However, the association between them in the presence of other factors known to influence these mental health disorders, and the context behind these mental health disorders and their association with alcohol consumption is under-researched in the older adult population. Aim of study: The aim of the study was to determine the associations of threshold depression, subthreshold depression, and GAD, with alcohol consumption; and the factors influencing these associations in an Irish community dwelling population aged 65 and over, and to explain them from the perspectives of healthcare practitioners. Methods: A cross-sectional mixed methods sequential explanatory design was used to achieve this aim. The sample for the quantitative phase consisted of 3499 adults aged 65 who participated in the second wave of The Irish Longitudinal Study of Ageing. Depressive symptoms were measured using the Centre for Epidemiologic Studies Depression Scale. GAD was measured using the Penn Worry State Questionnaire. Alcohol consumption was measured by quantity and frequency. This was categorised and coded as abstinent, moderate, at-risk, and harmful drinking. Reduction in consumption over the last two years was also categorised. Chi square tests and logistic regressions were used to examine bivariate relationships, and logistic regressions were used to examine the relationships between the GAD, depression variables and alcohol in the presence of multiple known sociodemographic, physical and psychological, health predictors (23 to 25 depending on the model). In the qualitative phase, semi-structured interviews were conducted with 10 healthcare practitioners (four general practitioners, five psychiatrists and one alcohol liaison nurse) on older adult mental health, particularly depression, and its association with alcohol consumption. Thematic analysis was used to analyses their interview transcripts. Findings: Harmful drinking, in addition to not reducing alcohol consumption over the past two years, was one of nine significant risk factors associated with having threshold depression (adjusted OR: 4.90; 95% CI: 1.22-19.65). While five factors did have an association with sub threshold depression, there was no significance between any category of consumption and subthreshold depression. Drinking moderately was associated with lower levels of GAD (adjusted OR: 0.64; 95% CI: 0.42-0.96) along with five other factors. Two main themes emerged in the qualitative analysis, Loss and Denial. The Loss theme there were three subthemes: loneliness, loss of meaning in life, and loss and harmful drinking. The Denial theme had three subthemes: denial of depression, denial of drinking, and denial as a way to manage depression, harmful drinking, and thus poor physical health. Conclusions and implications: The association of harmful drinking and depression illustrates the importance of screening for depressive symptoms and harmful drinking in the older population, while the themes of Loss and Denial illustrate this association?s complexity. There is a need to direct public awareness campaigns, on the topic of mental health, toward older adults as stigma may be a substantial barrier to seeking treatment.
APPROVED
Keywords: Mental health; Older adults; Alcohol consumption; Depression; Anxiety; Generalised anxiety disorder; Harmful drinking; Psychological